Influence of work discipline and non-physical work environment on employee performance at PT Bank Negara Indonesia Tbk Tangerang KCU - Chotamul Fajri; Mohamad Heikel (Enrichment : Journal of Management, 2023)
The purpose of this study was to determine the effect of work discipline and non-physical work environment on employee performance at PT Bank Negara Indonesia Tbk KCU Tangerang, either partially or simultaneously. The research method used in this research is quantitative research. The population used in this study were employees of PT Bank Negara Indonesia Tbk KCU Tangerang. The sampling method used by the author in this study is the saturated sample method, where the sample is the employees of PT Bank Negara Indonesia Tbk KCU Tangerang, totaling 87 employees. The data collection method used in this research is primary data. The primary data taken is the data from the answers of the respondents, amounting to 87 respondents. The results of this study indicate that work discipline has a partial effect on employee performance at PT Bank Negara Indonesia Tbk KCU Tangerang as evidenced by the value of tcount > ttable or (2,962 > 1,988). This is also strengthened by the value of Sig. < 0.05 or (0.004 < 0.05). The non-physical work environment has a partial effect on employee performance at PT Bank Negara Indonesia Tbk KCU Tangerang as evidenced by the value of tcount > ttable or (4,532 > 1,988). This is also reinforced by the value of Sig. < 0.05 or (0.000 < 0.05). Work discipline and non-physical work environment have a simultaneous effect on employee performance at PT Bank Negara Indonesia Tbk KCU Tangerang as evidenced by the value of Fcount > Ftable or (35.773 > 3.105), this is also strengthened by the value of Sig. < 0.05 or (0.000 < 0.05).